Development and applications of safranine-loaded Pluronic® F127 and P123 photoactive nanocarriers for prevention of bovine mastitis: In vitro and in vivo studies. (August 2019) - Combuca da Silva Junior, Ranulfo; da Silva Souza Campanholi, Katieli; Pedroso de Morais, Flávia Amanda; Soares dos Santos Pozza, Magali; Tadeu dos Santos, Geraldo; Hioka, Noboru; Caetano, Wilker
Abstract: Photodynamic therapy (PDT) is a therapeutic modality that exploits the formation of singlet oxygen through a photosensitizing compound. This compound is capable of eradicating sick cells or several strains of microorganisms. Its main advantage is associated with high selectivity and ability to avoid the self-resistance of pathogens, as often expected after the prolonged use of conventional antibiotics. These characteristics made it possible to the explore the performance of Safranine-O (Sf) photosensitizer incorporated in F127 and P123 Pluronic ® 4% (w/v) as nanocarriers solubilizer in the Photodynamic Inactivation of Microorganisms (PDIM) for post-dipping procedures in the prevention of bovine mastitis. Spectroscopic studies have shown the effective monomerization of Sf after being loaded into nanostructured micellar systems. The Sf-F127 and Sf-P123 showed bond molar absorptivity coefficients (ɛ) in the order of 10 3 L mol −1 and preferential relative locations in the hydrophilic hydrated micelle region (shell), as verified through the high Stern-Volmer constants (11.4 for Sf-F127 and 7.3 for Sf-P123) and proximity between apparent pKa (pKaap ) values (Sf-F127 ∼ Sf-P123) with a pKa of Sf in water. Sf singlet oxygen quantum yield in water was 0.24. This was determined by the indirect method of photodegradation of the chemical probe tryptophan. In vitro studies of the Sf-F127 and Sf-P123 systems proved to be efficient in inactivating the bacteria that cause bovine mastitis. In vivo evaluations in Dutch dairy cows demonstrated the viability of the system as a form of treatment or prevention of bovine mastitis in post-dipping procedures. Graphical abstract: Safranine-O (Sf) was solubilized into Pluronic ® nanocarriers, optimizing photophysical and photodynamic properties. In vitro and in vivo evaluations have shown promising results, involving Sf-mediated PDT in the prevention of subclinical mastitis. Image 1 Highlights: The studies showed the monomerization of Safranine-O incorporated into F127 and P123 nanocarriers with the preferential location in the micellar shell. Photophysical studies have shown that Safranine-O was able to generate singlet oxygen in water, even in the presence of small aggregates. In vitro studies of Sf-F127 and Sf-P123 systems proved to be efficient in inactivating the bacteria that cause bovine mastitis. In vivo evaluations of Dutch dairy cows demonstrated the feasibility of bovine mastitis treatment or prevention as post-immersion procedures. The quality physical-chemical and microbiological of milk produced by animals in treatment exhibited standards required by the Brazilian Normative Instruction.